UTILIZATION OF CINNAMON BARK (Cinnamomi burmannii cortex)AS A HERBAL PRODUCT: PEMANFAATAN KULIT KAYU MANIS (Cinnamomi burmannii cortex)SEBAGAI PRODUK HERBAL - Rina Kurniaty; Resmila Dewi; Cut Suraiya Wahyuni Utami; Erda Marniza; Widya Angreni (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Cinnamon is a species of the genus Cinnamomum, family Lauraceae, a woody plant commonly knownfor its use as a spice. A natural ingredient rich in benefits, with a distinctive aroma, is widely used forvarious purposes, including flavoring food and cakes. The most significant chemical componentspresent are cinnamic alcohol, coumarin, cinnamic acid, cinnamaldehyde, anthocyanin, and essential oil,along with sugars, proteins, simple fats, pectin, and other compounds. The extraction results ofCinnamomum burmanii bark contain the main antioxidant compounds in the form of polyphenols(tannins, flavonoids) and phenolic group essential oils, which have antimicrobial, antifungal, antiviral,antioxidant, antitumor, blood pressure-lowering, cholesterol-lowering, and low-fat properties. Thisactivity of making cinnamon bark herbal products in the form of rajangan, powder, and capsulepreparations can provide students with information, education, knowledge, and skills, as an alternativemedicinal preparation derived from natural ingredients.